Monetization of Dai Kondang's Da'wah as an Islamic Marketing Strategy in Improving the Ummah's Economy in the Digital Age - Kahfi, Al; Zen, Muhamad; Fatmawati, Fatmawati (FEB Universitas Sultan Ageng Tirtayasa, 2025)
The monetization of Islamic preaching in the digital era has rapidly expanded through the use of social media by popular preachers. This study aims to analyze how these preachers apply Islamic marketing strategies to monetize da'wah and its impact on their welfare, da'wah production teams, and the broader Muslim community. Using a descriptive qualitative method and literature study approach, this research explores monetization models such as digital advertising, sponsorship, premium memberships, crowdfunding, and the Marketing Mix 4P (Product, Price, Place, Promotion). The findings reveal that ethical monetization aligned with Islamic values can empower the ummah economically. Models emphasizing financial transparency and public benefit, such as crowdfunding and voluntary donations, are considered more in line with Islamic ethics than ad-based or exclusive paid content. However, balancing commercialization with spiritual integrity remains a challenge. Therefore, principles of Tawhid, Maslahah, Amanah, Adl, and Ihsan must guide da'wah monetization in the digital era.